293 Enhancing Your Recovery: A Mobile Application for Patients Undergoing Vascular Surgery. (4th May 2021) - Hodge, S; Pattabathula, K; Jenkins, J; Ogg, M
Abstract: Aim: With increasing demands on the healthcare system, a central (and currently essential) push for remote consultations, and an increasing number of co morbidities in the surgical population, the aim was to create an application that placed the focus on pre-hospital optimisation, education and autonomy – addressing these sector trends to enhance outcomes for patients and ease the burden on healthcare settings. Method: After obtaining baseline data, I worked alongside students from the Queensland University of Technology to produce an application suitable for both iOS and android platforms. Results: The application has four facets which mirror a patient's journey from their initial outpatient appointment through to recovery. The application is easy to use, free to download and readily accessible. On opening the application, the user can select their planned operation and navigate along a personalised decision tree. Conclusions: The application has been designed to educate and empower a patient to become an active participant in their care, leading to long-term changes in healthcare. Assessment is ongoing but early indications suggest that this will be a valuable tool in optimising outcomes for patients undergoing vascular surgery – leading to fewer post-operative complications and earlier restoration of functional status.